(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
We report results of a study that examines the external integration of a sample of firms in a region of Mexico from the theoretical perspective of managing the supply chain, through a study based on a questionnaire given to a director of each company. Operating profiles ranging from the operation identified in almost isolation of companies that have just the necessary contacts with the member companies of the supply chain to another what has high levels of external integration. In the analysis of the impact of external integration in their supply chains on three dimensions of competitive performance (in cost, flexibility and quality), an positive association was found only with flexibility.